Hubungan Pendidikan Ibu Hamil Dengan Pemilihan Pertolongan Persalinan Oleh Dukun di Desa Pukdale Kecamatan Kupang Timur - Diah Ayu Dwi Satiti; Ermi Lilianda Alang; Ninick Corea Fernandez (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
In Indonesia, especially in rural areas, the number of traditional birth attendants is still high, namely 75% to 80%. Delivery assistance performed by traditional birth attendants can cause various problems and is the main cause of maternal death which is high in perinatal and morbidity. Many factors influence the choice of assistance by adat, one of which is the factor of pregnancy education. This study aims to study the selection of aid distribution according to the traditional view of education for pregnant women in Pukdale Village, East Kupang District. This type of research is an analytic observational study using a cross sectional research design. The population is pregnant women who gave birth from January 2020 to December 2020 in the village of Pukdale, East Kupang District. The sample is pregnant women who gave birth in January 2020 to December 2020 in Pukdale Village, East Kupang District, a sample of 35 mothers who gave birth in a weaving village using a variable or complete saturation sampling technique. To determine the relationship between the education variables of pregnant women with the help of selection by Traditional labor uses the chi-square statistical test with =0.05. The results showed that 68% of the sample was aged 20-30 years, 54% of the sample had low education (didn't finish elementary school/didn't go to school, elementary or junior high school) and 66% of the sample gave birth with the help of a dukun. Mothers who gave birth to traditional healers, namely 73.9%, and mothers with low education gave birth to 83.3% of health workers with higher education. The results of statistical tests with a significance level (=0.05) showed that there was a relationship between the education of pregnant women and assistance in selecting births by traditional birth attendants. So it can be concluded that pregnant women's education is related to choosing traditional delivery assistance and recommends that health workers in the regions can provide health education to the community about the risks that can occur if pregnant women give birth at midwives and need to increase cooperation with traditional midwives (traditional partnerships) in labor matters.